Implementasi Model Pembelajaran Project Based Learning Terhadap Pengetahuan dan Keterampilan Membuat Petit Four di SMK Negeri 2 Jombang - Fitrotin Ni’ma Intan Sari; Asrul Bahar; Niken Purwidiani; Andika Kuncoro Widagdo (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
Jombang State Vocational School is a vocational education institution which is a vehicle for preparing professionals through various fields of expertise, one of which is the Culinary Department which equips students with skills, knowledge and attitudes in the field of Catering. However, in practical learning, problems were found in the form of low interest and enthusiasm for learning from students so that during practice students did not understand the material being taught. From the problems that occur, a research is carried out with the title Implementation of the Project Based Learning Learning Model on the Skills of Making Petit Fours at SMK Negeri 2 Jombang Using True Experimental Design with Pre-test Post Test Control Group Design to find out the results of the skills of making petit fours on subjects pastry and bakery products in Class XI Catering at SMK Negeri 2 Jombang which gives independent sample t-test results of 0.000 which means H0 is accepted and Ha is rejected so as to improve practical skills for students in developing collaboration, communication, solving and management skills supported by results. Keywords: PjBL, Practice, Improvement, knowledge, skills